Comparative Study of Soil Quality for Reclamation Based on Soil Fertility in Block 1 Pit 3 & Pit 5 Against Bank Soil at PT. Soe Makmur Resources, South Central Timor, East Nusa Tenggara Province - Funay, Chindy (ReTII, 2019)
This research was conducted on Block 1 pit 3 & pit 5 at PT. Soe Makmur Resources, South Central Timor, East Nusa Tenggara Province. The issue in this research is that there is a very small amount or even no top soil at all at the site and that there are no overburden management in the holes of the past excavation activities for reclamation. Which could lead to a soil fertility degradation. It is necessary to test the fertility of the pilled overburden with the controller of bank soil using the method of Electrometry, Titrimetry, Kjeldahl, Volumetric, Spectrophotometric and AAS to determine soil quality and future land management attempts. The test results shows pH content, C-Organic, N-Total, P-Total, cation exchange capacity and base cations exchangeable K, Ca, Na, Mg on pit 3 consecutively 5.69; 0.60%; 0.072%; 0.099%; 22.5 me/100g; 1.25 me/100g; 11.3 me/100g; 4.54 me/100g; 4.39 me/100g. On pit 5 consecutively 4.09; 0.30%; 0.165%; 0.042%; 21.8 me/100g; 1.36 me/100g; 11.84 me/100g; 3.26 me/100g; 4.84 me/100g. Whereas for the bank soil is 6.72; 0.45%; 0.044%; 0.048%; 19.22 me/100g; 1.60 me/100g; 8.50 me/100g; 4.92 me/100g; 3.27 me/100g. Based on the soil fertility criteria, the pilled overburden materials and bank soil are still considered low.